HUMAN CAPITAL BASIS OF DEVELOPMENT OF INNOVATIVE ECONOMY - Khodzhaevich, Abdurakhmanov Kalandar (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with topical issues of the formation and development of human capital. The development of the material, intellectual and spiritual capabilities of a person, the accumulation of human capital which is becoming an important task of the state, has been studied. The formation of human capital is associated with investments in man and his development as a creative and productive resource. The development of human potential in the Republic of Uzbekistan involves the implementation of the "Five Priority Initiatives of the President of the Republic of Uzbekistan". The five initiatives will help develop human capital, which will ensure priority investment in human capital with transformative potential. The task is to move rapidly along the path of building a society in the country in which all children eat fully, come to school ready to learn, can expect to get real knowledge at school and, having matured, are able to enter the labor market healthy, skilled and productive workers. Human capital is the knowledge, skills and health that people accumulate during their lifetimes, which allows them to realize their potential as useful members of society. In Uzbekistan, measures were taken to preserve and develop the country's intellectual potential through systemic reforms in the education system. The main goal of education was to prepare a diversified personality of a citizen, to increase the interest of young people in music, arts, literature, theater and other forms of art, which are oriented towards the traditions and needs of domestic and world culture, a modern system of values capable of active social adaptation in society and continuing professional education to self-education and self-improvement.